Saúde mental na Atenção Primária à Saúde: um estudo a partir do Programa Nacional de Melhoria do Acesso e da Qualidade da Atenção Básica - Hugo André da Rocha (2017)
Introduction: Introducing mental health in the context of the actions developed in Primary Health Care (PHC) is a challenge that has been placed on the agenda since the primary discussions of the Brazilian Sanitary and Psychiatric Reforms. Offering comprehensive, ongoing, territory-based care requires PHC professionals to be qualified and supported by specialists through follow-up, lifelong education strategies, and sharing of care. Objective: To identify the items of the National Program for Improving Access and Quality of Primary Care (PMAQ-AB) that better discriminate the capacity to offer mental health care. Methods: A cross-sectional study was carried out based on data from the 2nd cycle of the PMAQ-AB, referring to the 30,523 participating primary care teams. Data collection took place in the external evaluation phase of the PMAQ-AB, in the period 2013-2014. The analysis of the items was based on the Gradual Response Model of the Item Response Theory (TRI). In order to analyze the internal consistency, the Cronbach's alpha coefficients, Spearman's correlation and bisisserial point were used. Assumptions of unidimensionality and local independence of the items were tested. The clouds of words were used as one of the forms of presentation of the results. The means of the scores were compared to evaluate differences between the teams by strata of municipalities. Results: The items with the highest evaluation capacity were: program the agenda according to the risk stratification; keeps record of the most serious cases of users in psychological distress and offer some group service. Regarding the lease parameter, the items that required a higher level of mental health care offer were: offer some group care and offer educational and mental health promotion actions. The total Cronbach alpha coefficient was 0.867. They presented a higher correlation with the total score: recording the most severe cases of users in psychological distress and scheduling the agenda according to the risk stratification. Final scores ranged from -2.07 to 1.95. The proportion of teams classified as aboveaverage had a greater proportion in stratum 6, while the lowest proportion in this level was observed in stratum 2. In relation to teams classified as much below average the largest proportion was found in stratum 2 and the lowest proportion of teams classified in this group was observed in stratum 1. Discussion: The selected items presented a good capacity to differentiate the teams participating in the PMAQ-AB in relation to the offer of mental health care. Risk stratification for management of care, follow-up of the most serious cases, group care, and prevention and mental health promotion actions were the most important factors in discriminating the level of mental health care provision. Aligned with the assumptions of the Brazilian Psychiatric Reform, matriciation is inserted as a possibility because it breaks with the logic of fragmented care, having as a goal that all professionals involved in care are in line, even if they are in different services. Final considerations: Investments in factors such as risk stratification for care management, recording and follow-up of the most severe cases of people suffering from mental illness, group care, and prevention and mental health promotion actions are important to provision of mental health care by primary care teams.